Cycle of the werewolf ebook A novel. - King, Stephen (2019)
The classic masterpiece by #1 New York Times bestselling author Stephen King—illustrated by the legendary artist Bernie Wrightson! Terror began in January—by the light of the full moon... The first scream came from the snowbound railwayman who felt the werewolf's fangs ripping at his throat. The next month there was a scream of ecstatic agony from the woman attacked in her cozy bedroom. Now scenes of unbelievable horror unfold each time the full moon shines on the isolated Maine town of Tarker's Mills. No one knows who will be attacked next. But one thing is sure. When the full moon rises, a paralyzing fear sweeps through Tarker's Mills. For snarls that sound like human words can be heard whining through the wind. And all around are the footprints of a monster whose hunger cannot be sated...